الكفاءة التربوية لمعلمي اللغة العربية في المدارس الثانوية ببندا أتشيه - Novita, Bella Disa; Hayati, Salma; Fadhilah, Fadhilah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2023)
This study aims to determine the level of pedagogic competence of Arabic language teachers in MTs throughout Banda Aceh. This research is quantitative research with the research method taken is the survey method. The research instrument used was a questionnaire distributed to a number of 21 Arabic teachers at MTs throughout Banda Aceh City. Data analysis used descriptive statistics (Mean, Percentage, Standard deviation, and Frequency). The results showed that the level of pedagogic competence of Arabic language teachers in MTs throughout Banda Aceh was in the high category. This research implies that the pedagogical competence of teachers is very good in carrying out Arabic language learning.